Transport and depositional processes of organic matter evaluated by biomarker profiles in Miocene turbiditic sequences from Hokkaido, Japan - Ismail, Muhammad Adam; Asahi, Hiroyasu; Sawada, Ken (Sedimentary geology, 2023)
Extrabasinal turbidity currents, also known as hyperpycnal flows, can deposit vast amounts of organic carbon to the marine realm. On the other hand, intrabasinal turbidity currents are commonly thought to resuspend and further oxidize organic matter (OM), creating deposits with poor preservation of terrestrial OM. However, recent studies have shown that intrabasinal turbidity currents can still preserve terrigenous OM after reworking previously deposited OM-rich sediments. As such, both types of turbidity currents may act as unconventional source rocks. Considering that there is a discrepancy between global carbon burial fluxes in the marine environment and the amount of organic carbon delivered by rivers, OM preservation within such sandy deposits should not be overlooked. We investigated both plant fragment-rich extrabasinal and intrabasinal turbidites of the Miocene Kawabata Formation (Hokkaido, Japan) by using biomarker distributions within different facies formed by changes in sediment concentration due to progressive deposition during waning flow. Clear distinctions in terms of sedimentological features and organic geochemical characteristics between different facies were found and are interpreted to be caused by different OM sources and sedimentological processes. The sandy extrabasinal turbidites have high amounts of organic carbon, high pristane/phytane ratios, and fewer amounts of marine algal biomarkers due to direct transport from the terrestrial environment without mixing with marine waters. Intrabasinal, Bouma-type turbidites generally have poor OM, and low pristane/phytane values but high concentrations of algal biomarkers since sediments are sourced from the marine environment. In both extrabasinal and intrabasinal turbidites of this study, the plant fragment-rich sandy layers deposited by flows with lower sediment concentrations preserve high amounts of terrigenous OM, possibly due to having densities allowing woody plant fragments to remain within the flow and corresponding deposit, while basal Ta sandstones and Te hemipelagic deposits contain more marine OM due to erosion plus incorporation of marine sediments and mixing with marine waters respectively. Mud clasts formed in basal flows such as surge-like intrabasinal turbidity currents may also enhance OM preservation in plant fragment-poor sandstones. •Sandstones may act as organic matter deposition zones in addition to mudstones.•Plant-fragments can accumulate in sandy turbidites of low sand particle concentration.•Basal flows erode and incorporate marine-derived organic matter into the flow.•Mud clasts can enhance organic matter preservation.